A Dual-Core Model of Organizational Innovation - Daft, Richard L. (Academy of Management Journal, 1978)
This paper examines the role of administrators and technical employees in the process leading to innovation adoption. A marked division of labor is found. The evidence indicates that two distinct innovation processes?bottom-up and top-down?can exist in organizations. The findings are used to propose a dual-core model of organizational innovation.